2019
DOI: 10.1007/s00440-019-00919-z
|View full text |Cite
|
Sign up to set email alerts
|

Liouville metric of star-scale invariant fields: tails and Weyl scaling

Abstract: We study the Liouville metric associated to an approximation of a logcorrelated Gaussian field with short range correlation. We show that below a parameter γ c > 0, the left-right length of rectangles for the Riemannian metric e γφ0,n ds 2 with various aspect ratio is concentrated with quasi-lognormal tails, that the renormalized metric is tight when γ < min(γ c , 0.4) and that subsequential limits are consistent with the Weyl scaling.2010 Mathematics Subject Classification. Primary: 60K35. Secondary: 60G60.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 37 publications
0
25
0
Order By: Relevance
“…The present article is closely related to [8,15]. In [8] it was shown that discrete Liouville first-passage percolation (shortest-path metric where the vertices are weighted by the exponential of the discrete GFF) has subsequential scaling limits for sufficiently small γ > 0.…”
Section: Two Closely-related Workmentioning
confidence: 83%
See 4 more Smart Citations
“…The present article is closely related to [8,15]. In [8] it was shown that discrete Liouville first-passage percolation (shortest-path metric where the vertices are weighted by the exponential of the discrete GFF) has subsequential scaling limits for sufficiently small γ > 0.…”
Section: Two Closely-related Workmentioning
confidence: 83%
“…In [8] it was shown that discrete Liouville first-passage percolation (shortest-path metric where the vertices are weighted by the exponential of the discrete GFF) has subsequential scaling limits for sufficiently small γ > 0. On the other hand, in [15], the authors considered the case when the underlying field is a type of log-correlated Gaussian field (in the continuum) with short-range correlations (a so-called ⋆-scale invariant field) and showed that there exists a parameter γ * > 0 such that the corresponding Liouville first-passage percolation has a subsequential scaling limit for all γ < min(γ * , 0.4). The main contribution of the present article is that the result for Liouville graph distance is valid throughout the subcritical regime; i.e.…”
Section: Two Closely-related Workmentioning
confidence: 99%
See 3 more Smart Citations